1995
DOI: 10.1007/bf02967831
|View full text |Cite
|
Sign up to set email alerts
|

ENT and general practice: A study of paediatric ENT problems seen in general practice and recommendations for general practitioner training in ENT in Ireland

Abstract: A questionnaire survey of 225 general practitioners was carried out to establish the proportion of their workload formed by paediatric ENT problems. Approximately 50% of children seeking medical care from their general practitioners had problems in this area. Infections of the upper respiratory tract and associated organs were the most commonly dealt with complaints. The monthly referral rate by GPs of paediatric patients in their practice to an ENT outpatient clinic was 4.3%. As ENT problems are seen so commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 6 publications
1
75
0
2
Order By: Relevance
“…ENT problems account for 1.5% of Emergency Department attendances (overall commonest identified first diagnosis is dislocation/fracture/joint injury/amputation at 4.6%). 72% of GPs would see at least three children with ENT problems each day, and half of children that a GP sees will have ENT problems 1,2,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ENT problems account for 1.5% of Emergency Department attendances (overall commonest identified first diagnosis is dislocation/fracture/joint injury/amputation at 4.6%). 72% of GPs would see at least three children with ENT problems each day, and half of children that a GP sees will have ENT problems 1,2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of postgraduate training is such that not all non-ENT doctors will rotate through ENT, therefore ENT in the undergraduate curriculum assumes a relatively greater importance compared to other specialties 1,6 . However, a 2004 study in the UK found that only 78% of medical schools had a compulsory ENT attachment, and the average length of time spent in ENT was a week and a half 7 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This rises to 50 per cent in paediatric consultations. 4 Clinical expertise of GPs must, therefore, be adequate to enable early assessment and appropriate treatment of the common ENT diseases. This expertise is also essential to minimize inappropriate referral of patients who should be managed in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the medical class will become family physicians (14), where 20-30% of their practice is likely to be otolaryngological (15)(16)(17). Very little curricular time is spent on common otolaryngological problems.…”
Section: Discussionmentioning
confidence: 99%